Dampak Nilai Tugas Rendah terhadap Prestasi Akademik Siswa pada Mata Pelajaran PPKn di SMP Negeri 35 Percut Sei Tuan - Alex Prayoga Sidabutar; Daniel David Sidebang; Dorlince Oktavia Hutapea; Dwi Valentina Sihite; Jihan Aisyah Ramadhania; Nur Arba Asari; Abdi Nur Batu Bara (Journal Innovation In Education, 2024)
The subject of Pancasila and Citizenship Education is one of the subjects that must be studied at all levels from elementary school to university. In studying Pancasila and citizenship education, students must be able to understand what they are learning in order to become wise and good citizens. Based on research conducted by the author, there are several obstacles that cause low student learning outcomes at SMP Negeri 35 Percut Sei Tuan. Namely the readiness and maturity of students, their learning motivation, the learning media they use, and the learning methods used by their teachers.